Transformative Actions from Learning Assessment: A Cross-Context Typology, Coding Protocol, and Baseline Evidence from a Public University - Hector A. Aponte-Alequin; Layza N. Frias Rivera (European Scientific Journal, ESJ, 2025)
Institutions often collect abundant evidence of student learning yet struggle to translate it into meaningful change. This article addresses that gap by introducing a portable typology and transparent coding protocol for classifying “transformative actions” that emerge from learning assessment and lead to pedagogical, curricular, and student-support improvements. Using qualitative content analysis of records from an online assessment system and institutional dashboards at a large public university in the Caribbean, we compiled and coded 213 documented actions reported by graduate and undergraduate programs during 2022-2025. Nearly half of the actions involved course-level pedagogical modifications (43%), while formal curricular changes were rare (2%). A substantial share lacked sufficient descriptive detail to classify (31%), indicating a documentation challenge that can undermine institutional learning from assessment. We also observed emerging student-led initiatives and meta-assessment practices focused on improving rubrics, calibration, and feedback cycles. Beyond reporting distributions, the article contributes (a) a cross-context typology with coding rules and examples, (b) a reproducible template for program-level reporting and follow-up, and (c) baseline indicators to monitor progress in closing the assessment-to-action loop over time. We discuss implications for moving from compliance to improvement, strengthening the linkage between evidence and decision-making, and scaling effective practices to the curricular level.